Residual stress and domain switching in freeze cast porous barium titanate. Issue 4 (April 2022) - Roscow, J.I.; Li, Y.; Hall, D.A.
Abstract: Links between residual stress and domain switching in porous barium titanate ceramics were investigated using synchrotron X-ray diffraction as a function of an applied electric field. Barium titanate with highly aligned pores (with pore fraction v p = 0.52) was manufactured by freeze casting and compared with barium titanate produced via conventional pressing and sintering (with v p = 0.06). The domain switching fraction in the freeze cast ceramic was approximately double that of the low porosity barium titanate at a field of 3 kV/mm, attributed to a reduction in the residual stress from 70 MPa to 40 MPa with increased pore fraction. Whilst extrinsic domain switching was enhanced, the intrinsic lattice strain contribution to the piezoelectric properties was slightly reduced in the freeze cast barium titanate compared to the conventionally processed ceramic. These results point towards novel methods for engineering the functional properties of piezoelectric ceramics in the future.